Gambaran kecanduan internet pada remaja - Balqis Urwatul Wutsqo; Wirda Hanim; Eka Wahyuni (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2023)
This study aimed to look at internet addiction in adolescents, in this case impulse control disorders or the inability to control internet use. The term internet refers to any type of online activity. Internet is used to refer to all the contacts an individual has with web-based services, including websites, internet-based games, social media, and online entertainment. The type of research used is quantitative and descriptive. The sample in this study was 207 students. The sampling technique uses simple random sampling. Respondent data collection was carried out using questionnaires. The results showed that 9% of students had severe dependence on the internet. And from the aspect of internet addiction developed by Kimberly S. Young, there are as many as three aspects that have the highest percentage according to the respondents' circumstances: salience (7.17%), excessive use (7.17%), and lack of control (6.67%). It is recommended that for future research, it is necessary to develop other moderator variables or interventions so that later it can help students or adolescents reduce the problem of internet addiction they feel.